Experimental Investigation into Banana Fibre Reinforced Lightweight Concrete Masonry Prism Sandwiched with GFRP sheet - Vijayalakshmi, Ramalingam; Ramanagopal, Srinivasan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper presents the stress-strain behaviour of Natural Banana microfibre reinforced Lightweight Concrete (LWC) prisms under axial compression. The compressive strength of masonry is obtained by testing stack bonded prisms under compression normal to its bed joint. LWC blocks of cross-sectional dimensions 200 mm x 150 mm were used to construct the prism with an overall height of 630 mm.
Keywords: lightweight concrete; banana fibre; masonry prism; GFRP; experimental investigation; beton lekki; włókna bananowe; pryzmat; badania eksperymentalne